2012
DOI: 10.1371/journal.pone.0047851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Bt Maize to Sows during Gestation and Lactation on Maternal and Offspring Immunity and Fate of Transgenic Material

Abstract: BackgroundWe aimed to determine the effect of feeding transgenic maize to sows during gestation and lactation on maternal and offspring immunity and to assess the fate of transgenic material.Methodology/Principal FindingsOn the day of insemination, sows were assigned to one of two treatments (n = 12/treatment); 1) non-Bt control maize diet or 2) Bt-MON810 maize diet, which were fed for ∼143 days throughout gestation and lactation. Immune function was assessed by leukocyte phenotyping, haematology and Cry1Ab-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 52 publications
(59 reference statements)
3
14
0
2
Order By: Relevance
“…Consumers have many difficulties in avoiding genetically modified (GM) products due to the ubiquitous presence of GM crops produced worldwide (Buzoianu et al, 2012). Although regulatory agencies issued precise frameworks for adoption of transgenic crops, concerns about the safety of transgenic products still remain (Walsh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consumers have many difficulties in avoiding genetically modified (GM) products due to the ubiquitous presence of GM crops produced worldwide (Buzoianu et al, 2012). Although regulatory agencies issued precise frameworks for adoption of transgenic crops, concerns about the safety of transgenic products still remain (Walsh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Results of Cry1Ab toxin concentrations determined in porcine tissue samples were available from pig feeding studies (WALSH et al, 2011BUZOIANU et al, 2012). Organ samples were heart, kidney, spleen, liver, muscle, lymph node, brain, and serum of pigs fed with GM MON 810 (PR34N44) and non-GM isogenic maize (PR34N43).…”
Section: Matrix Effectmentioning
confidence: 99%
“…To study possible occurrence of Cry1Ab in porcine tissues, feeding studies with PR34N44 Bt-maize were performed (WALSH et al, 2011;BUZOIANU et al, 2012;WALSH et al, 2012), and results indicated that appearance or detection success of Bt toxin in different tissues is not uniform. Cry1Ab was positively detected in stomach content and digesta samples, but fell below the LOD for other tissues.…”
mentioning
confidence: 99%
“…Επιπλέον, μεγάλος όγκος μελετών έχει διεξαχθεί για τη μελέτη της θρεπτικής αξίας και της ασφάλειας των γενετικώς τροποποιημένων ζωοτροφών μετά τη χορήγησή τους σε διάφορα είδη αγροτικών ζώων (Flachowsky et al 2012). Τέλος, ικανός αριθμός άρθρων έχει δημοσιευτεί σχετικά με τύχη του 'ξένου', διαγονιδιακού ή ανασυνδυασμένου DNA των γενετικώς τροποποιημένων ζωοτροφών στο γαστρεντερικό σωλήνα των ζώων (Chainark et al, 2008, Guertler et al, 2008, Tremblay et al, 2008, Wiedermann et al, 2009, Rizzi et al, 2012, Johannessen et al, 2013, καθώς και με τις αποδόσεις παραγωγικών ζώων πού καταλώνουν τέτοιες ζωοτροφές (Alink et al, 2008, Buzoianu et al, 2012a, b, Snell et al, 2012, Walsh et al, 2012, Buzoianu et al, 2013.…”
unclassified
“…Η μελέτη αφορούσε στη χορήγηση γενετικώς τροποποιημένης τροφής σε χοιρίδια επί 110 ημέρες (Walsh et al 2012, Buzoianu et al 2012b, σε σύες στη διάρκεια της εγκυμοσύνης και της γαλακτικής περιόδου (Buzoianu et al 2012a) και σε σύες και τα χοιρίδια αυτών επί 115 ημέρες μετά τον απογαλακτισμό (Buzoianu et al 2013). ως γενικό συμπέρασμα, οι εν λόγω μελέτες κατέληξαν ότι δεν παρατηρήθηκαν ανωμαλίες στις διάφορες φυσιολογικές καταστάσεις των ζώων.…”
unclassified